PENGARUH SISTEM INFORMASI MANAJEMEN LINGKUNGAN TERHADAP GOOD GOVERMENT GOVERNANCE - Hertati, Lesi; Safkaur, Otniel (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2020)
An Environmental Management Information System is an information system that produces outputs using inputs that can process all the information needed to meet the organization's objectives for management activities. A good Environmental Management Information System is able to balance the costs and benefits to be gained, meaning an environmental management information system that will save costs, increase revenue that arises from very useful information. The organization must realize that meticulous technology can design and implement an environmental management information system to suit its desires in determining cost limits from the point of benefit to be obtained, then the resulting Environmental Management Information System will provide benefits and money. Integrated and flexible information technology is an environmental management information system tool, in information processing in order to design an environmental management information system that is able to serve the main task. The purpose of the environmental management information system is to meet the general information needs of all managers in the company or within the organizational subunits of the company. The environmental management information system provides users with information in the form of reports and outputs from various mathematical simulation models. The results of this study indicate that the environmental management information system can provide good or bad changes in Good Government Governance that are managed by the company. This research was conducted at PT Bukit Asam Indonesia located in South Sumatra. Keywords: Environmental Management Information System, Good Government Governance